Kinetic Study on the SO2 Adsorption using CuO/γ-Al2O3 Adsorbent - David Bahrin; Subagjo Subagjo; Herri Susanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Adsorbent CuO/g-Al2O3 for adsorption of SO2 were prepared by impregnating Cu(NO3)2.3H2O solution. Five types of adsorbent were obtained 5Cu (intended Cu concentration of 5%, actual of 4.92%), 8Cu (7.68%), 15Cu(14.13%), 22Cu (20.80%) and 27Cu (25.80%). For activity test, model gas containing SO2 with a concentration of about 0.755 mol/m3 were passed through the bed of 1 gram adsorbent at a flow rate in the range of 1.4-1.8 mL/s. Adsorption of SO2 were carried out at a constant temperature of 300, 350, 400 or 450 °C. Increasing sulfur loadings (gram of sulfur per gram of adsorbent) were observed with increasing adsorption temperatures, but not with increasing Cu content in the adsorbent. Among those types, adsorbent of 8Cu was considered as the best with respect to the sulfur loading (3 g of sulfur per 100 g of adsorbent). Adsorbent 5Cu had actually a better sulfur loading, but it was suspected being contributed also by adsorption of SO2 on Al2O3. The shrinking core model was used in the kinetic study of adsorption using 8Cu and with additional assumption of a spherical particle. Compared to film diffusion and pore diffusion controlling step models, the reaction rate limitation was the best to fit the experimental data. The reaction rate constant for this model at temperatures of 300, 350, 400 and 450 °C were 0.022, 0.038, 0.042, and 0.059 kg.m.mol-1.min-1, respectively. The activation energy was 21.25 kJ.mol-1 and the frequency factor was 2.02 min-1.